Searching for new frontiers : - Worland, Rick (Wiley, 2018)
The book covers significant genres and evolving thematic trends, highlighting a variety of movies that confronted the era’s major social issues. It notes the stylistic confluence and exchanges between three forms: the traditional studio movie based on the combination of stars and genres, low-budget exploitation movies, and the international art cinema. As the author reveals, this complex period of American filmmaking was neither random nor the product of unique talents working in a vacuum. The filmmakers met head-on with an evolving American social conscience to create a Hollywood cinema of an era defined by events such as the Vietnam War, the rise of the civil rights movement, and the moon landing.